Práticas das coordenadoras pedagógicas nas escolas municipais de Carambeí – PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This research aimed to study the pedagogical coordinator’s practices in municipal schools in Carambeí, PR. The general objective was to analyze the practices developed in these schools and their impact on teachers’ work. The specific objectives were to identify, characterize and situate them in the context where they are produced as well as to identify the implications of the pedagogical coordinator’s practices to the teachers’ work. The theoretical background supporting the discussions included: Placco (2002); Placco, Almeida and Souza (2010) and Pinto (2011) - pedagogical coordinators; (MARTINS,1998) - epistemological axis of the Theory as Expression of Practice; Saviani (1999); Bissolli da Silva (2003) and Cruz (2011) – historical contextualization; Santos (1992) and Tumolo and Fontana (2008) – understanding teachers’ work; and Santos (1992) – collective systematization of knowledge. This qualitative research is considered a case study due to its specificity. The research methodology included participant observation with recordings of field notes; use of questionnaires applied to teachers and pedagogical coordinators from municipal schools; organization of discussion groups and the documental analysis of the law that regulates the pedagogical coordinator’s function along with the analysis of 17 action plans of the candidates running for election. The data was analyzed in the Content Analysis perspective (BARDIN, 2016). The results of the analysis pointed out the attributions of the pedagogical coordinator’s position and the existence of three specific moments since the creation of the municipal education system: appointment of the counselor and supervisor by the Education Secretariat for the position of teaching advisor; selective test for the position of teaching support and, election of pedagogical coordinators. When analyzing the Action Plans, challenges and possible actions from practical issues are highlighted. Regarding characterization and identification, resistance practices were observed due to the existing unfavorable structural and human conditions. Finally, the implications of the pedagogical coordinator’s work to the teachers’ work indicate that: there is a proximity relation evidencing how significant their action is in the learning and teaching process; the coordinators’ assistance is mainly bureaucratic; planning is carried out through suggestions of activities, methodologies and material preparation with some moments of study; when assisting students, the priority is on disciplinary and learning issues; mock tests and evaluations; accompanying teachers in the classroom and providing them with some support occur whenever they face difficulties in their daily routine; pedagogical coordinators provide mediation between the several school segments, and in addition to students and teachers, they also provide assistance to parents, the school community, school workers and the direction team; the experience pedagogical coordinators have as teachers is fundamental to help teachers in their difficulties and doubts. Therefore, these practices can be said to impact teachers’ work regarding the help provided and that they are permeated by several determinants of the capitalist society production system. The development of collective work and a continuous education project is necessary for both teachers and pedagogical coordinators.
Keywords: Prática pedagógica; Coordenador pedagógico; Trabalho docente; Trabalho coletivo; CNPQ::CIENCIAS HUMANAS::EDUCACAO